The differences of psychological characteristics between male and female tennis players - Alim, A. (Advances in Social Science, education and Humanities research, Vol 278, 2018)
The psychological aspect is the important factor for the successful performance of tennis. The purpose of this study is to determine the difference between the psychological characteristics of male and female tennis players. This study used the survey research design. The data were collected on the day of the competition by 134 tennis players. The psychological questionnaire (motivation, self-efficacy, attitude, anxiety, and stress) was used to know the psychological characteristics of tennis players. The data were analyzed by an independent ttest. The result showed that there were significant differences in psychological characteristics between male and female tennis players (p = 0.023). Based on the results, it showed that gender has an influence on the different psychological characteristics of tennis players.